(untitled) - Silberschatz, Abraham; Korth, Henry F. (New York)
Bibliography: p.1281 - 1314; 10 parts: Relational Databases; Database design; Data storage and querying; transaction management; system architecture; Data warehousing, data mining and information retrieval; specialty database; advanced topics; case studies; Appendices
Keywords: Database management; Công nghệ thông tin -- Cơ sở dữ liệu